Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/bjh.16578
|View full text |Cite
|
Sign up to set email alerts
|

Experience with provisional WHO‐entities large B‐cell lymphoma with IRF4‐rearrangement and Burkitt‐like lymphoma with 11q aberration in paediatric patients of the NHL‐BFM group

Abstract: Summary Large B‐cell lymphoma with IRF4 rearrangement, and Burkitt‐like lymphoma with 11q aberration are two provisional lymphoma entities in the 2017 revision of the WHO classification of lymphoid neoplasms. Despite being more frequent in young patients, knowledge regarding their true incidence and clinical features in unselected cohorts of paediatric and adolescent patients is limited. We screened for both entities among paediatric patients (<18 years of age) in the German NHL‐BFM (Non‐Hodgkin lymphoma Berli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 14 publications
(26 reference statements)
2
55
0
Order By: Relevance
“…Despite the poor prognostic factors in our patient, such as advancedstage disease, BM involvement, and low absolute lymphocyte count, low-intensity chemotherapy (DA-EPOCH-R) was effective. These outcomes strengthen the favorable prognosis of BLL-11q and suggest consideration of dose-reduced therapy for this subgroup of lymphomas [3,10].…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Despite the poor prognostic factors in our patient, such as advancedstage disease, BM involvement, and low absolute lymphocyte count, low-intensity chemotherapy (DA-EPOCH-R) was effective. These outcomes strengthen the favorable prognosis of BLL-11q and suggest consideration of dose-reduced therapy for this subgroup of lymphomas [3,10].…”
mentioning
confidence: 71%
“…
Dear Editor, Burkitt-like lymphoma with 11q aberration (BLL-11q) is a new provisional classification in the revised fourth edition of WHO classification of lymphomas that resembles Burkitt lymphoma (BL) morphologically and phenotypically, but has unique features, including gains in 11q23.2-23.3 and losses of 11q24.1qter, with no MYC translocation [1]. BLL-11q predominantly occurs in young adult males, and characteristic cytogenetic features have been frequently observed in post-transplant patients [2][3][4]. However, the association between BLL-11q and immune deficiency remains unclear due to the limited number of cases [2,[4][5][6].
…”
mentioning
confidence: 99%
“…From a clinical perspective, the course of BLL-11q has only been systematically reported in pediatric patients, where it was shown to compare favorably to other aggressive lymphomas 21 . In contrast, Sevilla et al reported MYC-negative Burkitt-like-lymphoma, prior to the discovery of the 11q-gain/loss-pattern, to harbor an inferior outcome, compared with MYCpositive BL 22 .…”
Section: Case #2mentioning
confidence: 99%
“…The presence of IRF4 rearrangements identified by FISH studies, together with BCL6 rearrangements and a uniform lack of BCL2 and MYC rearrangements, are the defining features of LBCL-IRF4 [116,120,124]. Some cases may additionally exhibit IRF4/IGH fusions but are negative for IRF4 rearrangement using commercially available break-apart probes [125]. The involvement of light chain genes has been rarely reported [116].…”
Section: Large B-cell Lymphoma With Irf4 Rearrangementmentioning
confidence: 99%